Urinary Exosomes Diagnosis of Urological Tumors: A Systematic Review and Meta-Analysis - Xu, Yipeng; Lou, Jianmin; Yu, Mingke; Jiang, Yingjun; Xu, Han; Huang, Yueyu; Gao, Yun; Wang, Hua; Li, Guorong; Wang, Zongping; Zhao, An (Frontiers in Oncology, 2021)
Purpose Exosomes could be released directly into the urine by the urological tumoral cells, so testing urinary exosomes has great potential for non-invasive diagnosis and monitor of urological tumors. The objective of this study is to systematically review and meta-analysis of urinary exosome for urological tumors diagnosis. Materials and Methods A systematic review of the recent English-language literature was conducted according to the PRISMA statement recommendations (CRD42021250613) using PubMed, Embase, Cochrane Library, Web of Science, and Scopus databases up to April 30, 2021. Risk-of-bias assessment was performed according to the QUADAS 2 tool. The true diagnostic value of urinary exosomes by calculating the number of true positive, false positive, true negative, and false negative, diagnoses by extracting specificity and sensitivity data from the selected literature. Results Sixteen eligible studies enrolling 3224 patients were identified. The pooled sensitivity and specificity of urinary exosomes as a diagnostic tool in urological tumors were 83% and 88%, respectively. The area under the summary receiver operating characteristic curve was 0.92 (95% CI: 0.89–0.94). Further subgroup analyses showed that our results were stable irrespective of the urinary exosome content type and tumor type. Conclusion Urinary exosomes may serve as novel non-invasive biomarkers for urological cancer detection. Future clinical trial designs must validate and explore their utility in treatment decision-making. Systematic Review Registration [ https://www.crd.york.ac.uk/prospero/], identifier [CRD42021250613].